1999
DOI: 10.1111/jon199994217
|View full text |Cite
|
Sign up to set email alerts
|

Brain Uptake and Plasma Metabolism of [11C]Vinpocetine: A Preliminary PET Study in a Cynomolgus Monkey

Abstract: Vinpocetine, a vinca alkaloid, is a widely used therapeutic agent in patients with acute and chronic stroke. To reveal the mechanisms of vinpocetine action in the brain, vinpocetine was labeled with 11C. Positron emission tomography (PET) was used to determine the uptake and distribution of [11C]vinpocetine in brain regions and the trunk of a cynomolgous monkey in two independent measurements. The concentration of vinpocetine and its labeled metabolites was determined in blood and plasma using high-performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 19 publications
3
24
0
5
Order By: Relevance
“…In recent PET studies with carbon-11 labelled vinpocetine in monkeys and healthy young male volunteers, we have confirmed that vinpocetine passes the blood-brain barrier readily and enters the brain in a relatively large fraction [6,7]. In healthy men on average 3.7% of the total injected dose was in the brain shortly after i.v.…”
Section: Introductionmentioning
confidence: 51%
“…In recent PET studies with carbon-11 labelled vinpocetine in monkeys and healthy young male volunteers, we have confirmed that vinpocetine passes the blood-brain barrier readily and enters the brain in a relatively large fraction [6,7]. In healthy men on average 3.7% of the total injected dose was in the brain shortly after i.v.…”
Section: Introductionmentioning
confidence: 51%
“…once favoured as a treatment for stroke (Bereczki & Fekete, 1999;Gulyas et al 1999), owing to its effects on cerebral blood flow and glucose utilization following ischaemia (Rischke & Krieglstein, 1990). Vinpocetine has also been shown to be a free radical scavenger and to protect PC 12 cells from P-amyloid toxicity.…”
Section: Vinpocetinementioning
confidence: 99%
“…However, the drug as a very high volume of distribution and readily partitions into the brain (Gulyas et al, 1999) and, presumably, other fatty tissues that are likely to include the peripheral nerves. Hence, true tissue exposure levels may be somewhat higher than the circulating plasma level and, in any event, are within the range that might be expected to produce some attenuation of sodium channel function.…”
mentioning
confidence: 99%